To protect and collect: a nationwide study of profit-motivated police crime - Stinson, Philip Matthew, Sr. (Criminal justice studies, 2018)
This study is part of a larger research project on police crime in the United States. Police crimes are those criminal offenses committed by sworn law enforcement officers who have the general powers of arrest. Profit-motivated police crime involves officers who use their authority of position to engage in crime for personal gain. This study reports the findings on 1,591 cases where a law enforcement officer was arrested for one or more profit-motivated crimes during the seven-year period 2005-2011. The profit-motivated arrest cases involved 1,396 individual officers employed by 782 state, local, special, constable, and tribal law enforcement agencies located in 531 counties and independent cities in 47 states and the District of Columbia. Our data is the first systematic study of profit-motivated police crime. The study describes the nature of this form of police misconduct in terms of several dimensions, including the characteristics of police who perpetrate these crimes, where it occurs, the specific criminal charges, and the contexts within which profit-motivated police crime is punished through police agencies and the criminal courts.